Viscoelasticity of gelatin surfaces probed by AFM noise analysis - Benmouna, Farida (Langmuir : the ACS journal of surfaces and colloids, 2004)
The viscoelastic properties of surfaces of swollen gelatin were investigated by analyzing the Brownian motion of an atomic force microscopy (AFM) cantilever in contact with the gel surface. A micron-sized glass sphere attached to the AFM cantilever is used as the dynamic probe. When the sphere approaches the gelatin surface, there is a static repulsive force without a jump into contact. The cantilever's Brownian movement is monitored in parallel, providing access to the dynamic sphere-surface interaction as quantified by the dynamic spring constant, kappa, and the drag coefficient, xi. Gelatin is used as a model substance for a variety of other soft surfaces, where the stiffness of the gel can be varied via the solvent quality, the bloom number, and the pH. The modulus derived from the static force-distance curve is in the kPa range, consistent with the literature. However, the dynamic spring constant as derived from the Brownian motion is much larger than the static differential spring constant dF/dz. On retraction, one observes a rather strong adhesion hysteresis. The strength of the bridge (as given by the dynamic spring constant and the drag coefficient) is very small